Lean Management to Reduce Waiting Time for Routine Blood Service at Blood Transfusion Service Unit Cipto Mangunkusumo Hospital - Siti Ayu Putriasih; Andreasta Meliala; Firman Firman (Center for Health Policy and Management, 2020)
Background:Blood supply at Cipto Mangunkusumo Hospital is done by the Blood Transfusion Service Unit which is responsible for the availability of safe, high-quality, and sufficient blood. The high number of routine blood demand at the same time makes the waiting time lengthen and exceed the standard time. The implementation of lean methods is needed to identify value added and work activities that do not add value in order to meet the waiting time standard for routine blood services.Methods: This is an action research conducted at UPTD RSCM from October to November 2019. Samples taken by consecutive sampling for 2 weeks during working hours and outside working hours, weekdays and weekend. Observation guidelines use value-added, non-value added, waiting time, cycle time, and lead time observation sheets. Waste is included in the DOWNTIME matrix. Followed by interviews and focus group discussions and the implementation of 5S and visual management (PRC order monitoring systems based on information technology).Results: Research on 50 samples of routine blood demand pre-intervention and 50 samples of post-intervention with PRC blood and first serial transfusion. The most samples pre- and post-intervention came from the Thalassemia Polyclinic, Inpatient Building A, and Emergency Room. Waste found includes over production, waiting, non-utilized talent, transportation, motion, and extra processing. Value added of routine blood service post-intervention decreased from 1 hour 26 minutes 49 seconds to 1 hour 22 minutes 52 seconds (5%). The post-intervention waiting time decreased from 48 minutes 19 seconds to 31 minutes 23 seconds (35%). The routine blood service lead time at the UPTD RSCM post-intervention decreased from 2 hours 35 minutes 31 seconds to 2 hours 7 minutes 47 seconds (18%). An efficient process of routine blood demand occurs with an increase in value added ratio from 56% to 65% (9%).Conclusion: Implementation of lean management, namely 5R and visual management (PRC order monitoring system based in information technology), can reduce the waiting time for routine blood services in UPTD RSCM. The routine blood service process at UPTD RSCM has become more efficient.Keywords: lean management, blood service, waiting time.